Effects of Circuit Training with High Intensity and Low Intensity on Anaerobic Endurance in Basketball Players - Lalu Moh Yudha Isnaini (International Journal of Multicultural and Multireligious Understanding, 2019)
High-intensity and low-intensity circuit training exercises can result in increased physical fitness for basketball players. . The purpose of this study in general is to obtain the implications of high-intensity and low-intensity Circuit Training for increasing anaerobic endurance.